Perilaku caring perawat terhadap kepuasan pasien; Sebuah literatur Review - Octaviani, Nurul; Wulandari, Rizki Yeni; Surmiasih, Surmiasih (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
Professional nurse service may be performed by a nurse in the performance of their duty. Caring will enable harmonious interpersonal relationships between nurses and patients,it can help and fulfill the patient's need to provide satisfaction. The research objective is to examine the results of several journals about nursing caring behavior to the patient's satisfaction. The research design used descriptive methods from the journal review literature. The results showed that nurses who have a good caring attitude, so patient satisfaction can be good in accordance with the quality of caring behavior performed by nurses. Based on the literature review noted that the application of nurse caring behavior has a close correlation with patient satisfaction. The more caring a nurse is, the more satisfied a patient will receive nursing care service.